KONSEP KEWARGANEGARAAN DALAM TAFSIR AL-AZHAR - Abd. Mun’em; Faishal Khair (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2022)
Abstract Functionally, citizenship was initiated in the West by Aristotle during the Ancient Greek period, in the sense that citizenship was held only by the state apparatus. Citizenship evolved from functional to national after the emergence of the nation-state. Citizenship also emerged in the Islamic world when al-Farabi categorized citizens into small, medium, and large communities. Al-Maududi also popularised the concept of muslim and dhimmi citizens within the Islamic state. Some of these ideas have influenced the concept of citizenship worldwide, including Indonesia. It is noteworthy that despite having a majority muslim population, Indonesia's laws are positive laws based on the agreement of the founding fathers, rather than religious law as in some Islamic countries. This research will trace the influence of the above ideas on Hamka by answering two main questions: why was Hamka so concerned about citizenship in Indonesia, and how does he explain the concept of citizenship in his tafsir? Fazlur Rahman's double movement hermeneutics is used to interpret the classical meaning in the context of Hamka's social reality, which intersects with Christianisation, secularisation, modernisation, and classical Minangkabau tradition. The analysis concludes that Hamka's concept of citizenship is closely linked to the political upheavals experienced during the Old Order and New Order periods. This can be traced through his discussions about state issues, including the system of government, the status of citizens, as well as their rights and obligations. Keywords: Hamka, Citizenship, Tafsir Al-Azhar